Do we actually need a new scale? Improving postpartum depression screening in Malaysia: a narrative literature review - Suleiman Alsabi, Rania Nafi’; Mohd Jamil, Amilia Afzan; Dasrilsyah, Rima Anggrena; Alimuddin, Aishah Siddiqah; Rajen Durai, Ruthpackiavathy (Penerbit Universiti Sains Malaysia, 2025)
Postpartum depression (PPD) is a major maternal health concern in Malaysia, impacting both maternal well-being and infant development. Despite the availability of several validated screening tools, concerns remain about their cultural appropriateness and diagnostic accuracy in Malaysia’s multiethnic context. This narrative review critically evaluates the psychometric properties, contextual relevance, and clinical limitations of PPD screening tools used in Malaysian healthcare. The objective is to assess whether current instruments sufficiently detect PPD in Malaysian women and explore the rationale for a culturally tailored alternative. A targeted literature search was conducted across six databases—PubMed, Scopus, Ovid MEDLINE, Wiley Online Library, Cochrane, and Google Scholar—for studies published between 2000 and 2024, using keywords such as “postpartum depression”, “screening tools”, “Malaysia”, and “psychometric validation”. The inclusion criteria focused on studies examining Malaysian populations and reporting on the implementation, psychometric properties, or contextual adaptation of common screening tools. The Edinburgh Postnatal Depression Scale (EPDS), Postpartum Depression Screening Scale (PDSS), and Patient Health Questionnaire-9 (PHQ-9) were the most commonly used tools. Although they demonstrated moderate validity and reliability, their use in Malaysia is limited by suboptimal linguistic translation, poor contextual adaptation, and inconsistent validation procedures. Furthermore, these tools often overlook key sociocultural determinants like postpartum confinement practices, stigma, and healthcare access disparities. This review highlights the inadequacy of foreign-developed PPD screening tools for Malaysian mothers. Thus, a culturally sensitive, empirically validated tool that incorporates biopsychosocial risk factors specific to Malaysia is warranted to enable timely detection, appropriate intervention, and improved maternal mental health outcomes.